Interaction of the yeast Swi4 and Swi6 cell cycle regulatory proteins in vitro. - Andrews, B J (1992)
In budding yeast, two transcription factors, Swi4 and Swi6, control the expression of important cell cycle regulatory proteins (the G1 cyclins, Cln1 and Cln2, and the cyclin-like Hcs26) as well as the HO gene, whose product initiates mating-type switching. Both Swi4 and Swi6 are components of a protein complex that forms at a repeated sequence element, SCB (SWI4, -6-dependent cell cycle box), found in the upstream regulatory sequences of target genes. We show, by using proteins synthesized in vitro, a direct association between Swi4 and Swi6. The cdc10-Swi6 or ankyrin motifs present in both Swi4 and Swi6 are dispensable for their association, which is mediated instead by a region near the C terminus of each protein. Furthermore, we show that interaction with Swi6 is not necessary for specific recognition of the SCB sequence by the Swi4 protein; we propose that Swi4 is responsible for binding to the SCB sequence while Swi6, through its association with Swi4, regulates activity of the complex.